A Study on the Application of the Iterator Pattern to Enhance Software Reusability: Studi tentang Penerapan Pola Iterator untuk Meningkatkan Reusabilitas Perangkat Lunak - Siti Herawati (NUANSA INFORMATIKA, 2026)
The iterator design pattern is an effective approach in software development to achieve greater modularity and reusability. This study analyzes the application of the iterator pattern in enhancing software reusability, particularly within the object-oriented programming paradigm. The research includes a literature review and hands-on implementation using Python and Java to evaluate the separation of iteration logic from data structures. The results indicate that the pattern supports the principle of separation of concerns, enabling the development of code that is more flexible, structured, and maintainable. Code evaluation shows improvements in readability and the ease of component reuse. Therefore, this study provides a practical contribution to the understanding of design patterns and is expected to serve as a useful reference for software developers in building efficient and sustainable systems